The Right to Cross-Examination and Witness Protection in Ethiopia: Comparative Overview - Melaku, Tadesse (Mizan law review, 2019)
Cross-examination particularly in the context of criminal trial is a human right recognized in international human rights law and the Ethiopian constitution. However, states are increasingly facing another pressing policy consideration – protecting prosecution witnesses who could otherwise be subject to intimidation, and who could even risk their lives for providing evidence in the administration of criminal justice. Witness protection has become an important public interest that justifies the restriction of the right to cross-examination. Without such protection, witnesses could be uncooperative for fear of reprisal and, in view of this, many countries (including Ethiopia) have introduced measures restricting face-to-face examination through, among others, the suppression of witness identity. A review of foreign academic literature and foreign case law reveals that, when considering demands for anonymity, courts exercise maximum caution to ensure that the right to cross-examine witnesses is not unduly infringed. The writer argues that a recent constitutional ruling by the Council of Constitutional Inquiry in favor of withholding the identity of prosecution witnesses has failed to properly balance between the right to cross-examine against protecting witnesses. The ruling is likely to have a negative effect on fair trial and can adversely affect the fundamental rights of accused persons in Ethiopia.